The Culture to five species of grains is one of the Mongolian values (Mongolian Journal of Arts and Culture, 2024)
Since the beginning of human existence in Mongolia, food and beverage culture has been formed through the direct consumption of natural products such as natural fruits, wild grains, onions, mushrooms, and medicinal plants, and at a certain stage of development, the food culture was transformed into the cooking process by boiling, flavoring, refining, mixing. When Mongolians are overwhelmed by the forces of nature, they pray to the gods, have faith in the hidden powers of heaven, and worship them for saving. Based on this faith, agricultural rituals emerged from the mindset of praying to the heavens and the earth, worshipping the mountains and hills, and making offerings to ensure growth and development. At the same time, genres of melodic and non-melodic oral poetry, related to farming rituals have been developed. We will study the oral culture and mentality associated with the five species of crops, which have existed since ancient times, concerning the most valuable priorities of Mongols.As a result of the study of the most valuable priorities of Mongols, implemented by the Mongolian National University of Arts and Culture, within the framework of the project “Treasure of Mongols”, the President of Mongolia issued a decree on December 22, 2020, to honor the “Treasury Sutra” which was an important event in creating the unity, common interests, national consciousness, and unified spirit of Mongolians. The “Treasury Sutra” declares the Mongolian people, family, statehood, homeland, Mongolian language, Heritage, Nomadic wisdom, Education, and Morality as the most valuable priorities of Mongols.This study aims to examine the rituals and symbols of the five species of grains concerning the theme “Heritage Culture - The Treasure” using historical, symbolic, analytical, summarizing, comparative, juxtaposition, and cultural narrative methods.Таван зүйлийн тарианд холбогдох соёл, монголчуудын үнэт зүйл болох ньХураангуй: Монгол нутагт хүн үүсэж, амьдарч эхэлсэн үеэс байгалийн жимс жимсгэнэ, зэрлэг үр тариа, сонгино, мөөг, гогод, эмийн ургамал зэрэг бэлэн бүтээгдэхүүнийг шууд хэрэглэж байгаад, хөгжлийн тодорхой шатанд тэдгээрийг амталж, болгож, хольж, боловсруулж хэрэглэх үйл явцад шилжсэнээр идээ, ундааны соёл бий болжээ. Хүн байгалийн тайлагдашгүй элдэв үзэгдэл, сүр хүчинд автахдаа, түүний цаана ямар нэгэн хүч чадалт далдын эзэн бий хэмээн үзэж хүншүүлэх, амьшуулах, юмшуулах зэрэг дүрийг бий болгон сүсэглэж, тэдгээрийг аргадах, гуйх, тайтгаруулах, залбирах зэргээс үүдэн янз бүрийн зан үйлүүд үүсжээ. Дээрх зан үйлээс улбаалан уул овоогоо тахиж, үр тариагаа ургуулах, өсгөж өгөхийг гуйн өргөл мөргөл үйлдэж, эзэншүүлэх сэтгэлгээнээс тариалангийн зан үйл бий болсон. Үүнтэй зэрэгцэн аялгуут ба аялгуут бус аман яруу найргийн холбогдох төрлүүд ч мөн адил хөгжиж ирсэн байдаг.Таван зүйлийн тариатай холбоотой зан үйл, бэлгэдэл нь хүмүүний зайлшгүй хэрэглээнээс үүдэн бий болсон идээ ундааны соёлын нэгэн бүрэлдэхүүн хэсэг болохын хувьд монголчуудын нэгэн үнэт зүйл мөн болно. Энэхүү таван зүйлийн тариатай холбоотой аман соёл, сэтгэлгээ нэн эртнээс үүсэн бий болсон ба үүнийг бид үнэт зүйлд холбогдуулан судлахаар зорьсон. Таван зүйлийн тарианы зан үйл, бэлгэдлийг монголчуудын эрхэмлэн дээдлэх “Өв соёл” үнэт зүйлд хамааруулан үзэхдээ, түүхэн зүй, бэлгэдэл зүй, задлан шинжлэх, нэгтгэн дүгнэх, харьцуулах, зэрэгцүүлэх, тайлан тайлбарлах зэрэг аргуудыг ашиглан судаллаа.Түлхүүр үгс: түүх, бэлгэдэл, хүмүүн, эд өлөг, сэтгэлгээ